2021
DOI: 10.1111/jcmm.16829
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress regulates osteoblast proliferation and apoptosis via the lncRNA TUG1/miR‐34a/FGFR1 axis

Abstract: LncRNAs and microRNAs play critical roles in osteoblast differentiation and bone formation. However, their exact roles in osteoblasts under fluid shear stress (FSS) and the possible mechanisms remain unclear. The aim of this study was to explore whether and how miR‐34a regulates osteoblast proliferation and apoptosis under FSS. In this study, FSS down‐regulated miR‐34a levels of MC3T3‐E1 cells. MiR‐34a up‐regulation attenuated FSS‐induced promotion of proliferation and suppression of apoptosis. Luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Many in vitro studies also verified that osteoblasts couldsensitively respond to a wide range of different shear stress, of which 0.5–2 Pa is the most commonly used range [ 7 , 9 ]. The appropriate stimulation of FSS greatly contributes to the development and reconstruction of bone tissues through the activation of the gene expression of Runx2 and Osterix, and the secretion of collagen type I (Col I), osteocalcin (OC), and alkaline phosphatase (ALP) in bone mesenchymal stem cells (BMSCs) and osteoblasts [ 10 , 11 ]. To date, much attention has been paid to the effect of FSS on bone remodeling [ 12 , 13 ], but less is known about the underlying molecular mechanisms, such as how FSS integrates with other processes, including autophagy, which contributes greatly to bone remodeling to stimulate the differentiation of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro studies also verified that osteoblasts couldsensitively respond to a wide range of different shear stress, of which 0.5–2 Pa is the most commonly used range [ 7 , 9 ]. The appropriate stimulation of FSS greatly contributes to the development and reconstruction of bone tissues through the activation of the gene expression of Runx2 and Osterix, and the secretion of collagen type I (Col I), osteocalcin (OC), and alkaline phosphatase (ALP) in bone mesenchymal stem cells (BMSCs) and osteoblasts [ 10 , 11 ]. To date, much attention has been paid to the effect of FSS on bone remodeling [ 12 , 13 ], but less is known about the underlying molecular mechanisms, such as how FSS integrates with other processes, including autophagy, which contributes greatly to bone remodeling to stimulate the differentiation of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that FSS can activate the ERK5-serine-threonine protein kinase B (AKT)-forkhead box O3a (FoxO3a)-Bim/FasL signaling pathway, inhibit the activation of caspase 3, and protect osteoblasts from apoptosis induced by TNF- α ( Bin et al, 2016 ). Wang X. et al ( Wang et al, 2021e ) found that the expression level of long-coding (RNA) lncRNA taurine up-regulated 1 (TUG1) increased in a time-dependent manner when MC3T3-E1 cells were exposed to 12 dyn/cm 2 FSS treatment for 30, 60, and 90 min. LncRNA TUG1 upregulated fibroblast growth factor receptor 1 (FGFR1) expression by sponging miR-34a, which promoted osteoblast proliferation and inhibited osteoblast apoptosis ( Wang et al, 2021e ).…”
Section: Mechanical Stimulation With Osteoblastsmentioning
confidence: 99%
“…Wang X. et al ( Wang et al, 2021e ) found that the expression level of long-coding (RNA) lncRNA taurine up-regulated 1 (TUG1) increased in a time-dependent manner when MC3T3-E1 cells were exposed to 12 dyn/cm 2 FSS treatment for 30, 60, and 90 min. LncRNA TUG1 upregulated fibroblast growth factor receptor 1 (FGFR1) expression by sponging miR-34a, which promoted osteoblast proliferation and inhibited osteoblast apoptosis ( Wang et al, 2021e ).…”
Section: Mechanical Stimulation With Osteoblastsmentioning
confidence: 99%
“…Mechanically, miR-34a inhibits OB differentiation by targeting 3'UTR of LDHA. Additionally, the up-regulation of miR-34a attenuated FSS-induced promotion of OB proliferation and survival via FGFR1 [61]. Chen et al [62] identified miR-34a exhibited unique dual regulatory effects on both hMSC proliferation and OB differentiation.…”
Section: Mir-34amentioning
confidence: 99%
“…XIST miR-214-3p Unknown Inhibit osteogenic differentiation of PDLSCs [109] miR-29b-3p RUNX2 Inhibit OB differentiation [110] miR-135 RANKL Inhibit OB differentiation [111] miR-375-3p AKT/mTOR Inhibit OB differentiation [112] DANCR Unknown WNT Promote osteogenic differentiation of PDLSC [113] Unknown EZH2↓, Runx2↑ Increase OB proliferation and decrease OB apoptosis [114] miR-758 Notch2 Suppress osteogenic differentiation of PDLSC [115] Jagged1 Notch Facilitate osteoclast formation and root resorption [116] TUG1 miR-222-3p Smad2/7 Facilitate osteogenic differentiation of PDLSC [117] Unknown Wnt/β-catenin Promote OB proliferation and differentiation [118] miR-545-3p CNR2 Promote OB proliferation and differentiation [119] miR-34a FGFR1 Promote OB proliferation and inhibit apoptosis [61] Unknown MafB Stimulate osteoclast formation [120] PCAT1 miR-106a-5p BMP2 Promote osteogenic differentiation of PDLSC [121] H19 miR-675 TGF-β1/Smad3/HDAC Promote osteogenic differentiation of hMSC [122] miR-22, -141 Wnt/β-catenin Potentiate osteogenesis [123] miR-138 FAK Unknown [124] miR-188 LCoR Promote osteogenic differentiation of mBMSC [125] miR-19b-3p Unknown Promote cell proliferation and osteogenic differentiation of BMSCs [126] miR-675 APC Promote osteogenic differentiation of BMSC [127] miR-149 SDF-1 Stimulates osteogenic differentiation of BMSC [128] miR-185-5p IGF1 Promote matrix mineralization [129] miR-140-5p SATB2 Promote osteogenic differentiation of BMSC [130] miR-467 HoxA10 Promote osteogenic differentiation of BMSC [131] miR-106 Angpt1 Promote osteogenesis and angiogenesis [132] miR-625-5p Wnt/β-catenin Promote BMSC proliferation and osteogenic differentiation [133] miR-541-3p Wnt/β-catenin Promote osteogenic differentiation of BMSC [134] miR-532-3p SIRT1 Promote osteogenic differentiation of BMSC [135] miR Wu [117] revealed that TUG1 accelerates the osteogenic differentiation by sponging m...…”
Section: Physiological Effects Referencesmentioning
confidence: 99%